A Study on Some New Reverse Hilbert-Type Inequalities and Its Generalizations on Time Scales. (18th July 2022) - Zakarya, M.; I.Saied, Ahmed; AlNemer, Ghada; M. Rezk, H.
Abstract : This study develops the study of reverse Hilbert-type inequalities on time scales where we can establish some new generalizations of reverse Hilbert-type inequalities via supermultiplicative functions on time scales by applying reverse Hölder inequalities. The main results will be proved by using Specht's ratio, chain rule, and Jensen's inequality. Our results (when T = ℕ ) are essentially new.